Effect of DFT Exchange Correlation Functionals and basis set Quality on the Calculations of the Magnetic Coupling Parameter J (Global Journal of Science Frontier Research, 2019)
Abstract not found
Keywords: magnetic coupling parameter; DFT calculations; copper dimers